GERMAN FINANCIAL MOBILIZATION. - Ludmer, A. Henry (The Accounting Review, 1943)
Foreign commodity prices are determined by the so-called "Vergleichzszeit-system" in Germany. This involves a base commodity price on October 17, 1936 and fixes the conditions under which these prices may be raised or lowered. In accordance with the order of July 15, 1937 foreign commodities can be resold only at a price which consists of the purchase price and an economically justified profit. Export commodities from Germany are ordered to be sold at any price, if necessary, even far below production costs, the loss being recovered through the so-called export tax from the "Zusatzausfuhrverfahren." All firms which show a gain from domestic commerce have to pay the export tax to support exporters. After a year of full production under regular audits, permanent control through cost accountants, readjustments of book values to their "real" status, and other control measures or pressures, the producers might show a cost regression and large profits. These were acquired through taxation or bonds, thus securing the means for repurchasing the special drafts. The circle is closed and the credit expansion canceled after having fulfilled the desired task.